Inscriptions in Texts - Bréard, Andrea (Annali di Ca’ Foscari: Serie Orientale)
This article considers texts in G. Vacca’s (1872‑1953) library as vertices in a sinological network. I analyse his annotations inscribed into books, offprints, maps, brochures, which he mainly collected during his sojourn in China (1907‑08). Focusing on mathematical books, I argue that inscriptions and printed texts together not only materialise Vacca’s turn from mathematics to sinology but also produce new forms of knowledge that resulted from translations between languages spoken in his network: Chinese, universal languages, and the languages of logic and algebra. Far from being an isolated stronghold of piles of paper transported from China to Europe and extended thereafter in scale and content, Vacca’s documentary legacy is a continuous space of circulation in itself.